Tents along Deep Lake, Chilkoot Trail, approximately 1899 - Warner, Arthur Churchill, 1864-1943 (1899)
After gold was discovered in the Yukon Territory, thousands of people left for the Klondike to join in the gold rush in the Summer of 1897. Deep Lake is near Lake Lindeman. On verso of image: Deep Lake, Alaska. A.C. Warner, Photographer, Seattle, Wash., 707 12th Ave. Skaguay, Dyea, Chilkoot Pass. Warner 111 Filed in Alaska series.